Konteks Personal Mcdonalisasi Banten Siap Saji di Kota Denpasar - Subawa, I Made Pasek (Sphatika: Jurnal Teologi, 2024)
Banten ready to serve as an option in the procurement of banten in the community in Denpasar City provides convenience by substituting the pattern from personal to market. This means that the procurement of necessities can be done by buying without having to make it directly. The emergence of Banten ready to serve or known as McDonaldization has had an extraordinary effect in society, not only becoming a business opportunity, but also growing the economy in the community with the emergence of various Banten agent industries. However, behind that, this pattern that has become an option and is increasingly enjoyed has led to the degradation of society, especially women. From the observation and analysis of the scene carried out, the emergence of Banten ready to serve is caused by women not being able to make banten, making banten need talent and skills, and buying banten because of the disease of ngekoh.